PROSES PENGELOLAAN UNTUK KEBERHASILAN KBK - ., Sarbiran (LPMPP Universitas Negeri Yogyakarta, 2004)
The Competency-Based Curriculum (CBC) is not only a philoso phy but also a methodology, which assists schools or other educational institutions to improve the quality ofstudents' behavior and competen cies. As the methodology deals with curriculum implementation, the teachers should have some alternative techniques ofprocessing class management suitable forteaching and learning activities. Some ofthe techniques are benchmarldng; brainstonning; cause and effect diagrams;